Scaffolds of calcium phosphate cement containing chitosan and gelatin - Renó,C. O. (2013)
Calcium phosphate cements (CPCs) have potential to be used on repairing damaged bones due to their moldability, bioactivity and bioresorbability. These materials combine calcium orthophosphate powders with a liquid leading to a paste that hardens spontaneously at low temperatures. Hence, CPCs could be applied as scaffolds to support cell/tissue growth. This paper studies CPC scaffolds processing by foaming cement's liquid phase in which was added gelatin and chitosan. The former acted to increase the foam stability while the ladder acted as a foaming agent. Moreover, these polymers would enhance scaffold's biological properties by controlling material's total porosity and in vivo resorption. The method proposed led to scaffolds with 58.71% porosity with sizes ranging from 160 to 760 µm and compressive strength of 0.70MPa. After foaming, pores' size, distribution and interconnectivity changed significantly leading to a material that could be applied on bone regeneration since it would allow nutrient's transport, cell attachment and an increase in material degradation rate.